1999
DOI: 10.1046/j.1365-2036.1999.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori treatment instead of maintenance therapy for peptic ulcer disease: the effectiveness of case‐finding in general practice

Abstract: Background: Maintenance therapy with acid‐inhibiting medication is common in general practice. Since the eradication of Helicobacter pylori has become the treatment of choice for peptic ulcer disease, H. pylori treatment could replace maintenance therapy in patients with an ulcer history.Aim: To determine the effectiveness of a full peptic ulcer disease history case‐finding strategy, together with subsequent H. pylori testing and treatment, in discontinuing maintenance therapy.Method: Patients were included fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Prach et al found that in a cohort of 145 patients receiving long term H 2 receptor antagonists for chronic duodenal ulcer disease only 11.7% were Helicobacter negative,34 a value close to the 10% we found in our study35 and the 13% in another Dutch study 36. Cost effectiveness and decision analyses also suggest that physicians can give antibiotics to patients with an ulcer history without a prior diagnostic test 37…”
Section: Targeting Patients With An Ulcer Historysupporting
confidence: 83%
See 2 more Smart Citations
“…Prach et al found that in a cohort of 145 patients receiving long term H 2 receptor antagonists for chronic duodenal ulcer disease only 11.7% were Helicobacter negative,34 a value close to the 10% we found in our study35 and the 13% in another Dutch study 36. Cost effectiveness and decision analyses also suggest that physicians can give antibiotics to patients with an ulcer history without a prior diagnostic test 37…”
Section: Targeting Patients With An Ulcer Historysupporting
confidence: 83%
“…40-44 UK studies showed that about one third of patients that regularly use acid suppressants had proven ulcer disease 40-42. A study performed in the Amsterdam area found a rate of 39.2%,43 whereas a study in central Holland found a lower rate of 18%,36 similar to that found in the south (20%) 45. Furthermore, many patients use these drugs without a formal diagnosis (endoscopy or barium meal)34 38-43 and a significant percentage of such chronic and uninvestigated patients will probably also suffer from recurrent ulcers.…”
Section: Targeting Patients Who Use Acid Suppressantsmentioning
confidence: 81%
See 1 more Smart Citation
“…Even though a large proportion of patients in primary care is on long‐term acid suppression, to our knowledge no large study has addressed the prevalence of H. pylori in this subgroup of patients nor assessed the merits of eradication H. pylori in those who are positive. A number of small studies that did attempt to answer these questions gave encouraging results, but they concentrated only on symptomatic benefit and included only patients with peptic ulcer dyspepsia (PUD) [14–17]. We therefore designed this large study to assess the prevalence of H. pylori and the symptomatic and economic benefits of eradicating this organism in patients on long‐term H 2 RA in six primary care practices in the north of England (Humberside region).…”
supporting
confidence: 74%
“…It may be explained by the hesitation that many GPs feel to change treatment in patients who are doing well on chronic acid suppression. More effort needs to be put in education about the benefit of HP eradication as a cost-effective alternative to acid suppression in these patients [24]. …”
Section: Discussionmentioning
confidence: 99%